Obstruction is associated with perineural invasion in T3/T4 colon cancer. (11th May 2019) - Nozawa, H.; Morikawa, T.; Kawai, K.; Hata, K.; Tanaka, T.; Nishikawa, T.; Sasaki, K.; Shuno, Y.; Kaneko, M.; Hiyoshi, M.; Emoto, S.; Murono, K.; et al.
Abstract: Aim: Perineural invasion (PNI) is a risk factor for recurrence and metastasis and consequently leads to decreased survival in patients with various malignancies. Recent studies showed that stent placement in obstructive colon cancer increases the frequency of PNI. We hypothesized that mechanical stress including obstruction itself may be associated with PNI. Method: We retrospectively reviewed 496 patients with pathological T3 or T4 colon cancer who did not receive preoperative treatment. Data were collected from medical charts and pathological findings. The relationships between PNI and other clinicopathological factors were analysed using univariate and multivariate analyses. Results: PNI was observed in 239 (48%) patients. Obstruction was markedly more frequent in PNI‐positive cancer (39%) than in PNI‐negative cancer (24%, P  =   0.0003). Multivariate analyses identified obstruction as one of the significant factors associated with PNI (OR 1.68, P  =   0.028). Moreover, in 414 patients without distant metastasis who underwent complete resection, PNI was an independent factor associated with poor recurrence‐free survival (hazard ratio 2.35, P  =   0.003). The coexistence of PNI and obstruction resulted in greater decreases in recurrence‐free survival than PNI‐negative and/or non‐obstructive cases. Conclusion: Our results suggest that obstruction is associated with PNI and consequently contributes to an increased postoperative recurrence in colon cancer.